Photoinduced Oxygen Evolution Catalysis Promoted by Polyoxometalate Salts of Cationic Photosensitizers - Soriano-López, Joaquín; Song, Fangyuan; Patzke, Greta R.; Galan-Mascaros, J. R. (Frontiers in Chemistry, 2018)
The insoluble salt Cs15K[Co9(H2O)6(OH)3(HPO4)2(PW9O34)3] (CsCo9) is tested as heterogeneous oxygen evolution catalyst in light-induced experiments, when combined with the homogeneous photosensitizer [Ru(bpy)3]2+ and the oxidant Na2S2O8 in neutral pH. Oxygen evolution occurs in parallel to a solid transformation. Post-catalytic essays indicate that the CsCo9 salt is transformed into the corresponding [Ru(bpy)3]2+ salt, upon cesium loss. Remarkably, analogous photoactivated oxygen evolution experiments starting with the [Ru(bpy)3]6K4[Co9(H2O)6(OH)3(HPO4)2(PW9O34)3]·40H2O (RuCo9) salt demonstrate much higher efficiency and kinetics. The origin of this improved performance is at the cation-anion, photosensitizer-catalyst pairing in the solid state. This is beneficial for the electron transfer event, and for the long-term stability of the photosensitizer. The latter was confirmed as the limiting process during these oxygen evolution reactions, with the polyoxometalate catalyst exhibiting robust performance in multiple cycles, upon addition of photosensitizer and/or oxidant to the reaction mixture.